Can helping the sick hurt the able? Incentives, information and disruption in a disability-related welfare reform - Nitika Bagaria; Barbara Petrongolo; John Van Reenen (Queen Mary University of London, School of Economics and Finance, 2015)
Disability rolls have escalated in developed nations over the last 40 years. The UK, however, stands out because the numbers on these benefits stopped rising when a welfare reform was introduced that integrated disability benefits with unemployment insurance (UI). This policy reform improved job information and sharpened bureaucratic incentives to find jobs for the disabled (relative to those on UI). We exploit the fact that policy was rolled-out a quasi-random across geographical areas. In the long-run the policy improved the outflows from disability benefits by 6% and had an (insignificant) 1% increase in unemployment outflows. This is consistent with a model where information helps both groups, but bureaucrats were given incentives to shift effort towards helping the disabled find jobs and away from helping the unemployed. Interestingly, in the short-run the policy had a negative impact for both groups suggesting important disruption effects. The policy passes a dynamic cost-benefit calculation, but the costs of the organizational disruption implies that benefits take about six years to exceed the one-off set-up costs making it unattractive for (myopic) policy-makers.
Keywords: H51; I13; J18; 330; Incentives; Public sector; Unemployment benefits; Performance standards